ANALISIS REAKSI PASAR SEBELUM DAN SESUDAH PENGUMUMAN BUYBACK SAHAM PERUSAHAAN TERDAFTAR DI BEI 2020 - Tatok Endhiarto; Ainul Rahmawati; Novi Puspitasari (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to analyze the difference in abnormal return and trading volume activity before and after the announcement of the buyback of shares of IDX-listed companies in 2020. This study used a quantitative event study approach. The population in this study amounted to 57 companies, and the research sample amounted to 34 companies with a purposive sampling method. The observation period of this study was three days before the announcement and three days after the announcement of the share buyback. The research applied Paired Sample t-Test test when data are normally distributed and Wilcoxon Signed Ranks Test if the data is abnormally distributed. The test results show no significant difference in return and trading volume activity at the time before and after the announcement of the company's share buyback policy. This result indicates that asymmetric information between external and internal parties of the company is not much different so that investors cannot get abnormal returns on an ongoing basis or in a short period.